2018
DOI: 10.3390/agriculture8120190
|View full text |Cite
|
Sign up to set email alerts
|

Planting Fruits and Vegetables in Homegarden as a Way to Improve Livelihoods and Conserve Plant Biodiversity

Abstract: Multi-story cropping systems are used to grow fruits and vegetables in rural homegardens, and it has been argued that they are crucial for the food and nutrition safety of rural populations. They also are considered as refuges for a number of plant species, and as one way to reduce pressure on the surrounding ecosystem by providing resources such as food, fiber, and firewood to farmers on their own farmland. This study was conducted to assess the contribution of fruits and vegetables in homegardens to househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
2
6
0
1
Order By: Relevance
“…The number of species recorded in this study (39 species from 150 home gardens) was comparable to the 40 fruit plant species reported in the Hintalo Wejerat district (Tsegazeabe et al 2012), but lower than that in Kerala, India, i.e., 86 species (George and Cristopher 2019) and in the Jabon Mekar village, Bogor District, Indonesia, i.e., 57 species (Prasetyo 2007). However, it was higher than the 30 species of fruit plants growing in the home garden of North Sumatra, Indonesia (Silalahi and Nismawati 2018), 30 species in Langsa, Aceh, Indonesia (Navia et al 2017), 18 species in the Burie District, Ethiopia (Abebe et al 2019), 13 species in South-Western Ethiopia (Mathewos et al 2018), and 4 species in Bulen District, North-Western Ethiopia (Beyene et al 2018). This variation in the diversity of fruit plant species was affected by the home garden size and the culture of the local community in the study area (Arora and Anjula 1996).…”
Section: Evenness (Equitability) Index (J')mentioning
confidence: 94%
“…The number of species recorded in this study (39 species from 150 home gardens) was comparable to the 40 fruit plant species reported in the Hintalo Wejerat district (Tsegazeabe et al 2012), but lower than that in Kerala, India, i.e., 86 species (George and Cristopher 2019) and in the Jabon Mekar village, Bogor District, Indonesia, i.e., 57 species (Prasetyo 2007). However, it was higher than the 30 species of fruit plants growing in the home garden of North Sumatra, Indonesia (Silalahi and Nismawati 2018), 30 species in Langsa, Aceh, Indonesia (Navia et al 2017), 18 species in the Burie District, Ethiopia (Abebe et al 2019), 13 species in South-Western Ethiopia (Mathewos et al 2018), and 4 species in Bulen District, North-Western Ethiopia (Beyene et al 2018). This variation in the diversity of fruit plant species was affected by the home garden size and the culture of the local community in the study area (Arora and Anjula 1996).…”
Section: Evenness (Equitability) Index (J')mentioning
confidence: 94%
“…Studies have also shown that the greater the dietary diversity, the greater the adequacy of micronutrients consumed by a given human group ( 4 , 14 , 15 , 25 27 ). Agricultural biodiversity within farms and home gardens was also associated with the nutritional quality of diets ( 29 , 30 , 32 , 35 ) and with the livelihood potential of families ( 33 ). However, despite the richness of local food biodiversity, nutrient intake levels in several cases in rural areas were below recommendations, and food insecurity was also recurrent ( 12 , 22 , 24 , 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified that the absence of taxonomic identification was more common among manuscripts produced by disciplinary teams from social sciences and health sciences. On the other hand, a group exclusively composed of biological and environmental sciences scholars failed to choose a proper dietary assessment tool to gather consumption data ( 33 ). Multidisciplinary teams that included professionals from nutrition, natural sciences, and social sciences designed more robust approaches, choosing adequate methods and indicators to assess food biodiversity within diets.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini dikaitkan dengan terbatasnya lahan pekarangan sehingga warga lebih cenderung memilih menanam umbi-umbian, sayuran, dan rempah yang membutuhkan waktu singkat untuk mencapai masa panen dibandingkan menanam pohon buah. Hasil ini sejalan dengan penelitian terdahulu bahwa sekitar 71% dari responden (khusus yang hanya menanam sayuran) menganggap ukuran lahan kecil menjadi alasan mereka untuk tidak menanam buah-buahan (Mathewos et al, 2018). Terlepas dari prioritas jenis tumbuhan yang ditanam di lahan pekarangan, berdasarkan observasi lapangan ditemukan banyak vegetasi di sekitar pemukiman di wilayah Kecamatan Tobelo.…”
Section: Inventarisasi Tanaman DI Kebun Pekaranganunclassified